Treatment effect modifiers in hospitalised patients with COVID-19 receiving remdesivir and dexamethasone. Issue 5 (4th May 2023) - Leding, Cæcilie; Bodilsen, Jacob; Brieghel, Christian; Harboe, Zitta Barrella; Helleberg, Marie; Holm, Claire; Israelsen, Simone Bastrup; Jensen, Janne; Jensen, Tomas Østergaard; Johansen, Isik Somuncu; Johnsen, Stine; Kirk, Ole; et al.
Abstract: Background: The combined effectiveness of remdesivir and dexamethasone in subgroups of hospitalised patients with COVID-19 is poorly investigated. Methods: In this nationwide retrospective cohort study, we included 3826 patients with COVID-19 hospitalised between February 2020 and April 2021. The primary outcomes were use of invasive mechanical ventilation and 30-day mortality, comparing a cohort treated with remdesivir and dexamethasone with a previous cohort treated without remdesivir and dexamethasone. We used inverse probability of treatment weighting logistic regression to assess associations with progression to invasive mechanical ventilation and 30-day mortality between the two cohorts. The analyses were conducted overall and by subgroups based on patient characteristics. Results: Odds ratio for progression to invasive mechanical ventilation and 30-day mortality in individuals treated with remdesivir and dexamethasone compared to treatment with standard of care alone was 0.46 (95% confidence interval, 0.37–0.57) and 0.47 (95% confidence interval, 0.39–0.56), respectively. The reduced risk of mortality was observed in elderly patients, overweight patients and in patients requiring supplemental oxygen at admission, regardless of sex, comorbidities and symptom duration. Conclusions: Patients treated with remdesivir and dexamethasone had significantly improved outcomes compared to patients treated with standard of care alone. These effects were observed in most patient subgroups.